Massive Uveal Relapse of Retinoblastoma Presumed to Be Choroidal Tumorous Involvement: Case Series - Fariba Ghassemi; Masoud Rahimi; Hamid Riazi-Esfahani; Alireza Khodabandeh; Babak Masoomian; Sara Taghizadeh; Shervin Sharifkashani (Case Reports in Ophthalmology, 2023)
We report the choroidal and ciliary body invasion by retinoblastoma (RB) in a salvaged eye after complete and successful primary treatment. Case 1: A 25-month-old boy was referred due to group B RB lesions based on the International Classification of RB (ICRB; groups A–E) in the right eye (OD). His left eye (OS) was enucleated because of advanced group E RB. After 47 months of uneventful follow-up (F/U), a new lesion recurred and was treated with transpupillary thermotherapy. Four months later, a fast-growing pigmented subretinal mass was detected that was treated by brachytherapy with the apical dose of 80 Gy. Three weeks later, the lesion regressed completely, and no recurrence happened after 6 years of F/U. Case 2: A 4-month-old girl with a deletion in chromosome 13 was referred for bilateral RB. OD was enucleated because of unresponsive RB and anterior segment involvement. In OS, group B lesions had multiple recurrences after systemic chemotherapy. After a while, a single mass appeared in the nasal periphery which was controlled well with brachytherapy. Four months later, AC involvement was controlled with IAC, intravitreal, and intracameral chemotherapy, but posterior synechia and cataract appeared later. One year after the last treatment, UBM showed a ring-shaped ciliary body mass. Her parents refused enucleation again, and she received intravenous chemotherapy. Two years later, magnetic resonance imaging showed orbital and optic canal involvement with a deformed globe. In conclusion, RB recurrence can appear as local choroidal and ciliary body involvement even after a time of complete remission. The role of B-scan and UBM in early diagnosis and successful treatment is valuable.